Quality of life in Croatia, the former Yugoslav Republic of Macedonia and Turkey Second European Quality of Life Survey - Schuh, Ulrich; Mateeva, Liliana; Gstrein, Michaela; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2011)
This report presents comprehensive analysis and policy-relevant findings on the quality of life in three EU candidate countries: Croatia, the former Yugoslav Republic of Macedonia and Turkey (the CC3). Findings are based on Eurofound's second European Quality of Life Survey (EQLS 2007). Quality of life is analysed in different social domains, based on objective as well as subjective indicators. The report addresses the perceived economic situation of households, family life, housing and local environment, health and access to health services, perceived quality of society, and subjective well-being, as well as interrelations between these factors. In investigating these domains in greater detail and comparing social groups within and between the countries, the report provides essential information both for understanding country backgrounds and for future policy planning.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- Croatia; Quality of life -- Turkey; Quality of life -- Former Yugoslav Republic of Macedonia; Croatia -- Social conditions -- 21th century; Turkey -- Social conditions -- 21th century; Former Yugoslav Republic of Macedonia -- Social conditions -- 21th century; Electronic books